Intention to Use Islamic Banking Products and Its Determinants - Lajuni, Nelson; Wong, Winnie Poh Ming; Yacob, Yusman; Ting, Hiram; Jausin, Alfera (International Journal of Economics and Financial Issues, 2017)
As there is an increasing trend of Muslims and non-Muslims accepting Islamic banking, it is crucial to reconnoitre customers’ intention to use Islamic banking products. Such rationale is based on theoretical foundation and empirical evidence that customers’ perception towards a particular product would lead to their intention to choose that product. The purpose of this study is to examine the determinants of intention to use Islamic banking products in an emerging and vibrant market. 200 copies of questionnaires were distributed, 131 usable copies were subsequently collected. The data were then analysed using PLS-SEM. The findings show that attitude, government support, and social influence possess explanatory and predictive capacity to envisage customers’ intention to use Islamic banking products. As banking service is localized to better serve the customers, this study extends the literature by providing insights into the subject matter in emerging markets. Keywords: Islamic bank; intention; attitude; social influence; government support; product pricing; religious obligation; PLS-SEM JEL Classifications: G2, Z1